Rolling circle amplification to screen yam germplasm for badnavirus infections and to amplify and characterise novel badnavirus genomes - Bömer, M.; Turaki, A.; Rathnayake, A.; Silva, G.; Kumar, P. Lava; Seal, S. (Bio-Protocol, LLC, 2018)
Since the first discovery of badnaviruses (family Caulimoviridae, genus Badnavirus) in yam (Dioscorea spp.) germplasm in the 1970s (Harrison and Roberts, 1973), several hundred partial badnavirus reverse transcriptase (RT)-ribonuclease H (RNaseH) sequences have been characterised (Kenyon et al., 2008; Bousalem et al., 2009), but only a few complete Dioscorea bacilliform virus (DBV) genome sequences have been reported (Phillips et al., 1999; Seal and Muller, 2007; Bömer et al., 2016 and 2017; Sukal et al., 2017; Umber et al., 2017). We have optimised a workflow involving total nucleic acid extractions and rolling circle amplification (RCA) combined with restriction enzyme analysis for the detection and amplification of DBVs present in yam germplasm. We have employed this approach successfully revealing three novel episomal yam badnaviruses (Bömer et al., 2016). We proposed this to be a complementary method to denaturing gradient gel electrophoresis, which enables a rapid indication of badnavirus diversity as well as the identification of potentially integrated badnavirus sequences in the host genome (Turaki et al., 2017). Here, we describe the step-by-step protocol to screen yam germplasm for badnavirus infections using RCA as an efficient research tool in the amplification and characterization of novel badnavirus genomes.